2016
DOI: 10.1017/s1751731115002062
|View full text |Cite
|
Sign up to set email alerts
|

Calf management practices and associations with herd-level morbidity and mortality on beef cow-calf operations

Abstract: The objective of this study was to investigate calf management practices on beef cow-calf operations and determine associations with herd-level morbidity and mortality of pre-weaned calves. A 40-question survey about management practices, morbidity and mortality was administered to cow-calf producers by distributing paper surveys and by circulating an online link through various media. A total of 267 producers completed the survey. Data were analyzed with descriptive statistics and multivariable linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 30 publications
5
32
2
Order By: Relevance
“…The average annual loss of immature animals of 2.98% is within the range of 1.4-9.5% reported in beef calves by elsewhere (Bunter et al, 2013 andMurray et al, 2016). It has been reported that a large proportion of beef calf mortalities occur within the first week of birth (Bunter et al, 2013 andMurray et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The average annual loss of immature animals of 2.98% is within the range of 1.4-9.5% reported in beef calves by elsewhere (Bunter et al, 2013 andMurray et al, 2016). It has been reported that a large proportion of beef calf mortalities occur within the first week of birth (Bunter et al, 2013 andMurray et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…Other studies have reported the method of castration, management of colostrum, sex of calf, calf birth weight, calving season, weather conditions at calving, intervention during calving, herd size and the rate of occurrence of respiratory diseases as risk factors for beef calf mortality (Elghafghuf et al, 2014 andMurray et al, 2016). The average annual loss of immature animals of 2.98% is within the range of 1.4-9.5% reported in beef calves by elsewhere (Bunter et al, 2013 andMurray et al, 2016).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Dystocia is a common problem that causes high economic loss on cattle farms [1,2]. Cows experiencing dystocia are at a higher risk for reproductive problems, calf loss, high cow morbidity, and mortality/culling, as well as low subsequent fertility [3].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the number of farm animals is associated with the complexities of management and veterinary care, and the deterioration of their health (Barkema et al 2015;Murray et al 2015;Wolf et al 2016;Song et al 2018). Obviously for this reason, as well as due to over-intensive exploitation, their morbidity and decrease in the productive longevity of dairy cows is occur (Curone et al 2018;Benvenuti et al 2018).…”
Section: Introductionmentioning
confidence: 99%